Catur Guru Values in Strengthening Character Education at the Non-Formal Pasraman Kertajaya Tangerang - Sukirno Hadi Raharjo; Untung Suhardi (Jayapangus Press, 2026)
Catur Guru as a strategic foundation in strengthening student character education at the Kertajaya Non-Formal Pasraman, Tangerang. Catur Guru, as the core of Hindu teachings that includes respect for Guru Swadyaya (God), Guru Wisesa (government), Guru Rupaka (parents), and Guru Pengajian (teachers at school), was chosen to strengthen character education based on moral and spiritual values. This study uses a qualitative approach with a case study method, which includes participatory observation, interviews with related parties, and document analysis regarding the implementation of Catur Guru at the pasraman. The results of the study indicate that the teachings of Catur Guru (guru swadyaya, guru rupaka, guru pengajian, and guru wisesa) at the Kertajaya Pasraman Tangerang have made a positive contribution to the character of the Hindu generation. Through guru swadyaya (religious habits, prayer), guru pengajian (exemplary behavior, discipline, responsibility), guru rupaka (respect for parents), and guru wisesa (discipline, responsibility, and social concern). This concept has succeeded in internalizing the values of all Catur Guru adaptively. As a result, students are able to develop noble personalities that balance tradition, preserving local wisdom, and adapting to modern developments. Despite the challenges of globalization and parents' limited time, opportunities for technology-based innovation remain wide open. This research is expected to serve as a reference for other non-formal educational institutions in integrating Hindu teachings to develop the character of a young generation with morals and integrity.